The use of an unmanned aerial vehicle to investigate habitat use and behavior of invasive blue crab in Mediterranean microhabitats - MARCHESSAUX, GUILLAUME; BIZZARRI, SERGIO; MARSIGLIA, NICOLETTA; PONZÈ, NICOLO; SARÀ, GIANLUCA (Mediterranean Marine Science, 2023)
The blue crab Callinectes sapidus has shown an immense capacity to adapt to new habitats in the Mediterranean Sea. Following the numerous reports of its proliferation along western Sicily, an investigation was conducted to identify any existing populations. In August 2021, a population of blue crabs was found in the natural reserve of Trapani which includes a large area of restored saltmarshes. In this study, by developing a tracking system using Unmanned Aerial Vehicles (UAV), we studied (i) the behavior of blue crabs on an hourly scale, and (ii) the weekly position of blue crabs in the saltmarshes to determine substrate preference. This study provides a new approach to better understand C. sapidus’ habitat use and their potential impact on local biodiversity. Blue crab activity was found to increase with temperature and tidal height, with a peak in activity observed at high tide and at maximum temperatures: the mean speed (m h-1) was higher (12.1 ± 8.7 m h-1) at T > 28 °C than at T = 23.7 °C (2.0 ± 3.2 m h-1). Considering habitat use, in 49 ± 13 % of the cases, blue crabs were observed on the sand, while 21 ± 14 % in the Cymodocea meadows, and 30 ± 15 % in the Ruppia meadows. These microhabitats provide a refuge for C. sapidus and should be prioritized and studied before management plans are designed and implemented to manage this important invasive species.